9. The Effectivity of Health Counseling To The Increase of Knowledge In Preventing Iron Deficiency Anemia In Pregnant Women - Darmawati Darmawati; Fithria Fithria; Elly Wardani; Nia Saumiana (Universitas Syiah Kuala, 2020)
Iron deficiency anemia is a leading cause of death as well as health problems in the mother and fetus. Impacts that can be caused include abortion, stunted fetal growth, preterm labor, antepartum bleeding, retention of the placenta, and preterm labor. Important information about reducing anemia which can reduce the incidence. One effort that can be done is with health education. The purpose of this study was to determine the effectiveness of health education on increasing knowledge in anemia of iron deficiency anemia in pregnant women. This type of research is an experimental study with the design of one group pre-test post-test. The sampling technique in this study is the quota sampling of 50 respondents. Data collection was carried out using questionnaire sheets and analyzing data using the Wilcoxon sign test. The results showed that health counseling was effective to increase the knowledge of the respondents (0,000),with the difference between pre-test and post-test, which was 3.02. It is expected for health workers to increase health education related to anemia in pregnant women, so they have good knowledge to avoid this.